Synthesis and Characterization of Modified Nanocellulose-Based Adsorbent for Removal of Cu2+ Ion Metal in Wastewater - Noorhaslin, Che Su; Ain Aqilah, Basirun; Nor Shahroon, Hameed Sultan; Devagi, Kanakaraju; Cecilia Devi, Wilfred (Materials Research Forum LLC, 2025)
The continuous release of heavy metal from various industrial activities has been recognized as one of the major causes contributing to water pollutant. Herein, a novel magnetite adsorbent consisting of nanocellulose (NC), magnetite nanoparticles (MNP) and titanium dioxide (TiO2) have been prepared using hydrothermal method. The adsorbent material with adsorption, magnetic and photocatalytic properties has been successfully synthesized and used for Cu2+ removal from industrial wastewater. The magnetite adsorbent made up of nanocellulose from sago was characterized by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy, (FTIR), field emission scanning electron microscope (FESEM) for physicochemical study. XRD demonstrating high crystallinity of nanocellulose and displays well crystallized anatase TiO2. TiO2 embedded on the surface on NC/MNP were clearly observed through FESEM. The photocatalytic efficiency of the adsorbent degradation of Cu was evaluated using atomic adsorption spectroscopy (AAS). The NC/MNP showed removal of 54.1% of Cu2+ metal. Increase of TiO2 loading (800µl) facilitate Cu removal up to 96% after 120 minutes exposure under ultraviolet irradiation. Kinetic analysis using the PSO model at 100mg/L of Cu2+ gave a value of equilibrium adsorption capacity, qe of 4.29 mg/g and a value of the pseudo-second-order rate constant, K2 of 0.004 (95% C.I., 0.0037 to 0.012). The result from these studies showed that the combination of nanocellulose, magnetite and TiO2 has potential heavy metal removals.